2010
DOI: 10.1007/s12011-010-8884-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Forms of Selenium Supplied to Pregnant Goats on the Levels of Selenium in the Body of Their Kids at the Time of Weaning

Abstract: The aim of this trial was to compare the effect of long-term supplementation of goats with different forms of selenium on body reserves of selenium in their kids at the time of weaning. Thirty-three pregnant goats were divided into five groups. Group C was control while the other four groups were supplemented with selenium (Se) for 6 weeks before parturition (0.3 mg/goat/day) and after parturition (0.9 mg/goat/day). Group "Se-I" received sodium selenite and three other groups received organic forms: "Se-L," la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…Many authors compared, in the first place, inorganic forms of selenium such as selenite and selenate and Se-enriched yeast and discovered higher concentrations of selenium in the blood (Pehrson et al, 1999; Pavlata et al, 2001; Guyot et al, 2007Phipps et al, 2008), body (Sevcikova et al, 2011), and in milk Givens et al, 2004; Muñiz-Naveiro et al, 2005 of animals supplemented with Se-enriched yeast. Pechova et al (2008) compared selenium concentrations in goat milk after per oral administration of selenium in the form of Se-enriched yeast, lactate-protein complex, and selenium proteinate and they discovered that the levels of selenium in milk were significantly higher only in the group supplemented with Se-enriched yeast than in the controls as well as in both groups supplemented with other forms of selenium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors compared, in the first place, inorganic forms of selenium such as selenite and selenate and Se-enriched yeast and discovered higher concentrations of selenium in the blood (Pehrson et al, 1999; Pavlata et al, 2001; Guyot et al, 2007Phipps et al, 2008), body (Sevcikova et al, 2011), and in milk Givens et al, 2004; Muñiz-Naveiro et al, 2005 of animals supplemented with Se-enriched yeast. Pechova et al (2008) compared selenium concentrations in goat milk after per oral administration of selenium in the form of Se-enriched yeast, lactate-protein complex, and selenium proteinate and they discovered that the levels of selenium in milk were significantly higher only in the group supplemented with Se-enriched yeast than in the controls as well as in both groups supplemented with other forms of selenium.…”
Section: Discussionmentioning
confidence: 99%
“…(Trávníček et al, 2008(Trávníček et al, , 2010Heindl et al, 2010;Skřivan et al, 2010a, b;Wang et al, 2011). In some experiments it was documented that the organic form of selenium (especially selenomethionine) is more available than inorganic forms (Pavlata et al, 2001; Gunter et al, 2003; Kuricová et al, 2003Weiss and Hogan, 2005; Guyot et al, 2007; Pechova et al, 2008Steen et al, 2008;Sevcikova et al, 2011;Pavlata et al, 2011a). However, several papers comparing various forms of Se supplementation have recently been published and some results not confirming better biological effect of organic-bound forms of selenium have occurred (Leeson et al, 2008;Heindl et al, 2010;Pavlata et al, 2011b).…”
mentioning
confidence: 99%
“…Tissue selenium content in different organs of the younglings were the highest in the Se-yeast group, but the other organic forms were also more effective as supplements than selenite. 27 Sodium selenite was also compared with dextrin stabilized selenium nanoparticles (both forms used at doses 10-100 μg/mL). An in vitro investigation revealed that the viability of the nanoparticle-treated cells was much higher than in the case of those treated by selenite.…”
Section: Comparison Of the Effect Of Different Selenium Forms On Orgamentioning
confidence: 99%
“…[21] have identified the antioxidant potential of Auricularia auricula-judae mushroom in their study. Xu et al [22], studied the antioxidant potential of Auricularia auricula. Hosseinihashemi et al, identified the antioxidant effects of T. versicolor in different solvents in their study.…”
Section: Dpph Free Radical Scavenging Activitiesmentioning
confidence: 99%